Hybrid swarm-based geographic VDTN routing - Azzoug, Youcef (2021)
“This is a post-peer-review, pre-copyedit version of an article published in Intelligent Technologies for Internet of Vehicles. The final authenticated version is available online at: https://doi.org/10.1007/978-3-030-76493-7_14”.